Efficacy of Angiotensin Receptor Blockers (Valsartan, Candesartan, Losartan) in Lowering Blood Pressure: A Systematic Review - Maharani, Shafa Shaomi; Destiani, Dika Pramita (Pharmacology and Clinical Pharmacy Research, 2025)
Hypertension is a significant health issue that significantly increases the risk of cardiovascular disease. Angiotensin II receptor blockers (ARBs) are commonly used in Indonesia to treat hypertension, yet comprehensive comparative efficacy data within this drug class remain limited. This review seeks to evaluate the blood pressure-lowering efficacy of three particular angiotensin receptor blockers (ARBs)—Valsartan, Candesartan, and Losartan—in individuals diagnosed with hypertension. This systematic review identified randomized controlled trials (RCT) obtained from PubMed and Google Scholar using several keyword combinations. Among 20 RCTs with 6.425 patients treated with three ARBs, all included studies demonstrated significant blood pressure reductions. The mean reductions in systolic blood pressure (SBP) and diastolic blood pressure (DBP) were the greatest for Candesartan (-18.69/-10.25 mmHg), followed by Losartan (-14.80/-7.8 mmHg), and Valsartan (-8.94/-7.58 mmHg). Candesartan achieved the largest reduction, decreasing baseline systolic blood pressure (SBP)/diastolic blood pressure (DBP) by 38.16/18.95 mmHg over 12 weeks. In contrast, Valsartan showed the smallest reduction, with SBP decreasing by 0.81/0.04 mmHg after 66 months. It can also be linked to the pharmacokinetic properties of the drugs, where Valsartan has a higher bioavailability, and Losartan has a lower bioavailability compared to the other ARBs. It can be concluded that ARBs, including Valsartan, Candesartan, and Losartan, are generally effective in reducing blood pressure in hypertensive patients, with Candesartan showing the greatest efficacy. Future research should involve direct comparative trials of Valsartan, Candesartan, and Losartan, along with studies on their molecular mechanisms, to increase effective hypertension treatments.